(untitled) (Proceedings of the International Conference on Public Health, 2021)
Digital health initiatives have become popular in all jurisdictions across the globe. The digital health move, though it is envisioned as a cost-effective way to ensure the availability of health care services especially for the people who live in rural areas, its success depends on the response of the health care system and the state control and regulation. India lacks a comprehensive statesponsored or state-regulated health care system and more than 70 percent of people utilise the private sector medical services. In this backdrop, the implementation of the National Digital Health Mission (NDHM), announced by the Government of India very recently, will be critical. Thus, this research paper strives to bring out the public-private disjunction in the availability and utilisation of public and private health care facilities, issues of health care financing and legal regulation of clinical establishments in the public and private sector. This study uses the doctrinal method and analyses the Five-Year Plans, National Sample Survey Reports, National Health Profile, National Health Accounts Estimates for India and other Government Reports and independent studies to detail the public-private dichotomy. However, this study finds limitations in presenting the current position of private health care service providers due to the unavailability of updated authoritative government reports/ studies/ surveys. On reviewing the currents trends in the public and private health care sector, the study finds that the private sector has surpassed the public sector in all means, including health provisioning, utilisation, and financing. The NDHM is a laudable initiative to ensure affordable health care to millions of people in India. However, any move to implement it, leaving the fundamental issue of deep-rooted public-private dichotomy existing in the healthcare sector will be detrimental. It will result in a digital divide in the public and private healthcare sector and gross violation of patients’ rights and mismanagement of health information.